Microbial mediated synthesis, characterization, antibacterial and synergistic effect of gold nanoparticles using Klebsiella pneumoniae (MTCC-4030). Issue 6 (11th January 2016) - Prema, P.; Iniya, P. A.; Immanuel, G.
Abstract : Herein, the microbial mediated synthesis of gold nanoparticles (GNPs) was achieved via an easy biological protocol using Klebsiella pneumoniae (MTCC-4030). Abstract : Herein, the microbial mediated synthesis of gold nanoparticles (GNPs) was achieved via an easy biological protocol using Klebsiella pneumoniae (MTCC-4030). Gold ions in the reaction mixture were exposed to K. pneumoniae for the formation of colloidal GNPs. The characterization study indicated that the UV-vis spectral analysis of the GNPs showed a peak at 550 nm. XRD spectroscopy of the GNPs confirmed their crystalline nature. Scanning electron images of the GNPs showed that they were spherical in shape and were well dispersed. Atomic force microscopy revealed that the size range of the GNPs was between 10 and 15 nm. The FTIR study revealed the possible involvement of reductive groups on the surface of the nanoparticles. The antibacterial activity of the GNPs showed the highest inhibitory zone (25.60 mm) against Escherichia coli as an indicator strain. The synergistic effect of the GNPs obtained the highest fold increase (4.06) and activity index (3.210) against E. coli, followed by 2.610 activity index against Staphylococcus aureus using amoxycillin and streptomycin as standard antibiotics, respectively.